Coping mechanism of informal trading enterprises in adverse situation: a case study of street vendors in the Narayanganj City, Bangladesh - Nayam, Kushnuma Tun (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Applied Economics, 2021.